(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: The nephroprotective drugs are having essential roles in reducing or preventing the possibility of toxicity with wide range of drugs used for severe infections or cancers and still now the researchers investigate many drugs with different mechanisms and examine their possibility to combined with nephrotoxic drugs in different ways in order to reduce their toxicity or prolong the limited duration of treatment. In same way, the present study designed to find the potential nephroprotective activity of sildenafil in reversing or reducing the nephropathies induced by gentamycin. Methods: The experiment was designed to include thirty-two rats and these were divided into four groups. The first ( control ) group received isotonic saline (2mL/kg/day i.p.). Second (positive control ) group were received only sildenafil (5 mg/kg/day orally p.o).Third (induction ) group received gentamycin (100 mg/kg/day i.p.). Fourth (treatment) group received sildenafil (5mg/kg/day p.o.) followed by gentamycin (100 mg/kg/day i.p.). The course of treatment continued to ten consecutive days . All animal were anesthsized at day 11th. and blood collected by special tubes by cardiac puncture in order to be used for investigating of serum creatinine, urea, total protein , albumin and kidney injury molecules-1(KIM-1). Also, the kidneys were harvested and kept in formalaldehyde 10% for evaluation of histopathological changes. Results: The gentamycin (induction)group showed all features of nephrotoxicity by producing a significant elevation of serum creatinine, urea , and KIM-1levels, with a significant reduction in serum total protein and albumin levels. Furthermore, the histopathological changes proved the nephrotoxicity in compared to control group. While sildenafil (treatment) group displayed the ameliorating effect on serum biomarkers and histopathological changes in comparison with both control (non-significant changes) and induction group (significant changes) at level of significant 0.05%. Conclusion; This study ended with conclusion, which can be summarized as potential nephroprotective of sildenafil in selected dose against gentamycin nephrotoxic dose in rat model.